Spanish exports and logistics needs. A spatial marked point pattern approach - Luisa Alamá; Laura Márquez-Ramos; Celestino Suárez (European Regional Science Association (ERSA), 2010)
This paper aims to analyse whether the existing logistic platforms network in Spain is covering the Spanish transport demand by using a spatial marked point pattern analysis (Baddeley, 2008). In particular, we use the demand of transport to export goods as a proxy of the demand of logistics infrastructure in Spain. Then, we obtain data of trade flows between Spanish regions (NUTS level 2), as well as data of exports from every Spanish region to European Union members in the year 2000 and 2007. We also obtain data about the different logistics platforms existing in Spain. We incorporate transportation network structure in spatial econometric models of commodity flows (LeSage and Polasek, 2008) and we also consider those variables traditionally included in gravity models (Deardorff, 1995), such as income and population, as extra information that the points have (marks) and which represents an "attribute" of the point. Obtained results should provide evidence about the location of the logistics platforms (land, maritime and intermodal) required in order to satisfy optimally the existing demand of transport infrastructure.
Keywords: R12; R23; R48; 330; Spanish regions; inter-regional trade; logistics platforms